Enriching the al-Quran supply chain: the impact of 4G networks - Mohd Salleh, Rezashah; Seth, Mohd Hareth; Shaharuddin, Nur Diyana; Syed Ahmad Razali, Syed Hasif Emir; T.K. Muthu Koya Thangal, Thahira Bibi; Mohd Zabidi, Mahfuzah (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
Businesses are compelled to keep up with the most recent innovations and to react to emerging global needs and opportunities as information and communication technologies develop quickly and exponentially. Supply chains are becoming continuously automated through digitization, which necessitates the consideration of innovative services to maintain the effectiveness and efficiency of the value chain. The new network enhancements incorporated in 4G networks enhance the significant expectations along the value chain given the impending technological breakthroughs. The importance of 4G telecommunications in supporting various value chain activities are highlighted in this study.